PERANAN SISTEM AGROFORESTRI POLA DUSUNG TERHADAP PENDAPATAN PETANI DAN KELESTARIAN LINGKUNGAN DI DESA HARUKU - Mustamu, Sofia (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
This research aims to assess the role of agroforestry in farmers' income and environmental sustainability in Haruku Village. The study used a purposive sampling method, selecting 20 respondents who apply the dusung agroforestry system in Haruku Village. Interviews and observations were conducted to collect primary data, while secondary data were obtained from the Haruku village government and other literature sources. The results indicate that there are 29 types of plants, including vegetables, fruits, tubers, and timber plants, commonly cultivated by the community in Haruku Village. Through the implementation of the agroforestry system, farmers' income is higher than non-agroforestry income. Agroforestry practices also contribute to environmental sustainability by reducing climate change impacts and decreasing the use of inorganic fertilizers among farmers.